Financial Literacy, Inclusion, and Behavior: Impacts on Economic Sustainability of Indonesian Migrant Workers in Sabah - Muhammad Agusalim; Efraim Bavo Priyana (AIBPM Publisher, 2026)
Indonesian Migrant Workers (IMWs) contribute significantly to the national economy through remittances; however, limited financial capability often constrains their long-term economic sustainability. This study aims to examine the effects of financial literacy and financial inclusion on economic sustainability, with financial behavior acting as a mediating variable among IMWs in Sabah, Malaysia. A quantitative survey approach was employed using proportionate cluster random sampling. Data were collected from 398 respondents and analyzed using SPSS and Structural Equation Modeling (SEM) with AMOS. The results reveal that financial literacy significantly influences economic sustainability (b = 0.116; p = 0.037), while financial inclusion shows a stronger direct effect (b = 0.552; p 0.001). Financial behavior also significantly affects economic sustainability (b = 0.333; p 0.001). Furthermore, financial behavior significantly mediates the relationships between financial literacy and economic sustainability (b = 0.062; Sobel = 2.466) and between financial inclusion and economic sustainability (b = 0.167; Sobel = 3.470). These findings highlight the importance of strengthening financial capability and inclusive access to financial services to enhance the long-term economic resilience of IMWs.